Analisis Kebutuhan Belajar Bahasa Arab melalui Media Sosial; Instagram - Sujefri, Alfan; Habibah, Ihda Filzafatin (Postgraduate of IAIN Metro Lampung Indonesia, 2023)
This study aims to find out the results of the analysis of the needs of learning Arabic by students through special social media, namely Instagram. The research method used is survey-based and supported by several documents and several supporting theories. Of course, the population in this study is a sample of students from several levels of education as active users of Instagram social media. This research was conducted as a new thing that emerged in the world of learning Arabic which so far was considered difficult by some students. In the research results, it was found that 2 factors were needed by Arabic language students through Instagram, namely internal factors and external factors. External factors are the material needs of the four maharah lugawiyah; istima' (native speaker audio material), kalam (dialogue between followers of Instagram accounts), qiraah (native Arabic literacy), and kitabah (there are discussions through chat rooms between Instagram followers). Internal factors from Instagram account users; physical fitness (using appropriate gadgets), intelligence (smart using digital literacy), interest and motivation to learn (attractive Instagram display design accompanied by fun educational games).